2012
DOI: 10.17305/bjbms.2012.2446
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of relatedness between neurocan gene as bipolar disorder susceptibility locus and schizophrenia

Abstract: Large scale genetic association meta-analyses showed that neurocan (NCAN) gene polymorphism rs1064395 is susceptibility locus for bipolar disorder. These studies also included patients with bipolar disorder originated from Bosnia and Herzegovina. Followed by theory of shared genetic elements between bipolar disorder and schizophrenia susceptibility, other studies explored several genetic factors with schizophrenia vulnerability as well. In this work, authors investigated the association between previously conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Their results showed that rs1064395 A-allele, known to be a risk factor for BD, was significantly overrepresented in schizophrenia patients compared to control group [17]. These results, sustained by similar data [18, 19, 70, 75], suggest that genetic variation in NCAN rs1064395 represents a common risk factor for BD and schizophrenia. The patients with schizophrenia showed significantly increased rates of BD in comparison with control subjects.…”
Section: Cspgs Structure-function Relationship In Genetic Disordersmentioning
confidence: 88%
See 3 more Smart Citations
“…Their results showed that rs1064395 A-allele, known to be a risk factor for BD, was significantly overrepresented in schizophrenia patients compared to control group [17]. These results, sustained by similar data [18, 19, 70, 75], suggest that genetic variation in NCAN rs1064395 represents a common risk factor for BD and schizophrenia. The patients with schizophrenia showed significantly increased rates of BD in comparison with control subjects.…”
Section: Cspgs Structure-function Relationship In Genetic Disordersmentioning
confidence: 88%
“…Also, the presence of NCAN mutants was associated with psychiatric disorders as bipolar disorder, schizophrenia, and ADHD [1719, 7074]. …”
Section: Cspgs Structure-function Relationship In Genetic Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic studies in humans revealed that the variation of NCAN, a gene encoding PNN component protein neurocan, is a common risk factor for schizophrenia and bipolar disorder (Mühleisen et al, 2012;Oruč et al, 2012;Schultz et al, 2014). Neurocan has also been shown to regulate brain development, dendritic spine remodeling and the function of GABAergic interneurons (Zhou et al, 2001;Mohan et al, 2018;Sullivan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%